Basic management accounting for the hospitality industry - Chibili, Michael N., ....- (Groningen : Noordhoff Uitgevers, 2016)
Basic Management Accounting for the Hospitality Industry uses a step by step approach to teach students about the concepts and applications of hospitality management accounting, and enables the students to independently master the content. The book deals with a range of topics: commencing with a basic introduction to management accounting; and ending with capital investment decisions. Why Basic Management Accounting for the Hospitality Industry? * English method focusing on non-native speakers; * sector specific theory and content; * supported by a website with extra study and teaching materials. The objective of the author is to provide an introduction to the basic management accounting concepts and applications based on Einstein's maxim that "everything should be made as simple as possible, but no simpler". This choice of simplification is due to the fact that the level of English used in the text takes into consideration that a good proportion of students in hotel or tourism-related education use English as a second language. The approach used in the book makes it very comprehensible. It takes the students clearly and logically through the concepts and applications of hospitality management accounting, and enables them to independently master the content.
Keywords: Hospitality management ; accounting; Toerisme ; budgettering; Toerisme ; prijsbeleid